Literature Review of Consumer Behavior: Customer Loyalty, Repeat Purchase and Purchase Interest - Setyo Widodo, Joko (Dinasti Publisher, 2021)
Consumer behavior in the current era of disruption varies greatly. To see this, of course, it is necessary to conduct further analysis and research on current consumer behavior. In looking at consumer behavior, researchers take the variables of customer loyalty, repeat purchases, and buying interest. The researcher conducted a descriptive qualitative research method by obtaining data through the Google Scholar and Mendeley application as a reference. The results of this research are 1) customer loyalty is related to consumer behavior, 2) repeat purchases are related to consumer behavior, and 3) buying interest is related to consumer behavior.